2021
DOI: 10.1038/s41598-021-92812-w
|View full text |Cite
|
Sign up to set email alerts
|

Noncytotoxic silver nanoparticles as a new antimicrobial strategy

Abstract: Drug-resistance of bacteria is an ongoing problem in hospital treatment. The main mechanism of bacterial virulency in human infections is based on their adhesion ability and biofilm formation. Many approaches have been invented to overcome this problem, i.e. treatment with antibacterial biomolecules, which have some limitations e.g. enzymatic degradation and short shelf stability. Silver nanoparticles (AgNPs) may be alternative to these strategies due to their unique and high antibacterial properties. Herein, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 98 publications
1
41
0
Order By: Relevance
“…They mentioned that the biosynthesized AgNPs were significantly more effective against S. aureus and P. aeruginosa than the chemically synthesized AgNPs using Polyvinylpyrrolidone (PVP) as a stabilizing agent. These results were also compatible with those reported by Skóra et al (2021) who investigated the antibacterial and antibiofilm activities of AgNPs against 18 medically important MDR bacteria including S. aureus and E. coli. They found that Acinetobacter baumannii and S. aureus strains, were the most affected.…”
Section: Discussionsupporting
confidence: 92%
“…They mentioned that the biosynthesized AgNPs were significantly more effective against S. aureus and P. aeruginosa than the chemically synthesized AgNPs using Polyvinylpyrrolidone (PVP) as a stabilizing agent. These results were also compatible with those reported by Skóra et al (2021) who investigated the antibacterial and antibiofilm activities of AgNPs against 18 medically important MDR bacteria including S. aureus and E. coli. They found that Acinetobacter baumannii and S. aureus strains, were the most affected.…”
Section: Discussionsupporting
confidence: 92%
“…So, it is difficult to enter into gram-positive bacteria than gram-negative bacteria ( Erjaee et al, 2017 ). Earlier studies have shown that AgNPs were active against a wide range of pathogenic bacteria due to their effective antibacterial properties ( Gandhi et al, 2021 , Skóra et al, 2021 , Urnukhsaikhan et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…But the role of AgNPs on human cells is unknown when their antibacterial capability is considered in the context of human use. For instance, silver nanoparticles were less toxic to eukaryotic cells, combined with their antibacterial capability, could be particularly valuable in endodontic treatment when bacteria in the root canal system must be eliminated ( Skóra et al, 2021 ). Silver NPs are also employed as antiseptic and disinfection agent because of their potential antibacterial property ( Das et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Ag NPs also show antifungal activity against C. albicans , C. tropicalis [ 56 , 57 ], and Fusarium oxysporum f. sp. radicis-lycopersici [ 58 ].…”
Section: Inps As Promising Antibacterial Agentsmentioning
confidence: 99%